PENGARUH CORPORATE GOVERNANCE, FINANCIAL INDICATORS, DAN UKURAN PERUSAHAAN PADA FINANCIAL DISTRESS - Cinantya, I Gusti Agung Ayu Pritha; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
Financial distress occurs on property & real estate company in Indonesia, PT Bakrieland Development, Tbk. This suggests that large companies are not necessarily protected from any financial distress. Prospective investors should be keen to invest the time, it is very necessary to ensure the safety of the invested funds. This study had purpose to determine the effect of corporate governance which consisting of institutional ownership, managerial ownership, the proportion of independent commissioners & the amount of the board of directors, financial indicators which consisting of liquidity & leverage and the size of the company toward financial distress. This research was conducted at the Indonesian Stock Exchange by accessing www.idx.co.id. The number of samples taken as many as 37 samples over three years used a nonprobability sampling method. Data was collected through non-participant observation method. This study used logistic regression as technique analysis. There are seven hypotheses were tested using logistic regression. Based on the results of the analysis found that institutional ownership and liquidity influenced financial distress. While managerial ownership, the proportion of independent commissioners, the number of board of directors, leverage and firm size did not influenced on the financial distress.
Keywords: corporate governance, financial distress